2014
DOI: 10.1530/rep-13-0631
|View full text |Cite
|
Sign up to set email alerts
|

Heat-shock protein A8 restores sperm membrane integrity by increasing plasma membrane fluidity

Abstract: The constitutive 70 kDa heat-shock protein, HSPA8, has previously been shown to contribute to the long-term survival of spermatozoa inside the mammalian female reproductive tract. Here, we show that a recombinant form of HSPA8 rapidly promotes the viability of uncapacitated spermatozoa, the ability of spermatozoa to bind to oviductal epithelial cells, enhances IVF performance, and decreases sperm mitochondrial activity. Fluorescence recovery after photobleaching revealed that the repair of membrane damage is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 50 publications
1
29
0
1
Order By: Relevance
“…The repair of membrane damage is mediated via increase in sperm membrane fluidity. The ability of HSPA8 to influence membrane stability and fluidity, alongside its conserved nature among mammalian species, supports the idea that this protein protects sperm survival through membrane repair mechanisms (121). Ongoing studies are elucidating the mechanisms that are involved in these protective effects and their potential impact on reproductive success and potential.…”
Section: Extracellular Cell Stress Proteins In Cancermentioning
confidence: 77%
See 1 more Smart Citation
“…The repair of membrane damage is mediated via increase in sperm membrane fluidity. The ability of HSPA8 to influence membrane stability and fluidity, alongside its conserved nature among mammalian species, supports the idea that this protein protects sperm survival through membrane repair mechanisms (121). Ongoing studies are elucidating the mechanisms that are involved in these protective effects and their potential impact on reproductive success and potential.…”
Section: Extracellular Cell Stress Proteins In Cancermentioning
confidence: 77%
“…Hsc70 appears to interact with components of the sperm cell surface membrane (117,118) and exposure to Hsc70 prolongs the survival of boar, bull and ram sperm (117,120). Studies have now shown that a recombinant form of Hsc70 (HSPA8) rapidly promotes the viability of uncapacitated spermatozoa, the ability of spermatozoa to bind to oviductal epithelial cells, enhances the performance of in vitro fertilisation procedures, and decreases sperm mitochondrial activity (121). The repair of membrane damage is mediated via increase in sperm membrane fluidity.…”
Section: Extracellular Cell Stress Proteins In Cancermentioning
confidence: 99%
“…The recombinant HSPA8 used in this study was prepared at the University of Sheffield's laboratory; the preparation and purification method has been described in detail by Moein-Vaziri et al [10]. An aliquot of the protein, dissolved in PBS and stored at À80 C, was thawed, diluted in more PBS to achieve the concentrations required by the experimental designs, and stored at À20 C before use.…”
Section: Source Of Heat Shock Protein A8mentioning
confidence: 99%
“…Although it often functions at the intracellular level, it has also been detected in the extracellular space, where it exerts protective effects on cell viability, apparently possessing both proapoptotic and antiapoptotic properties depending on the situation [3,4]. Within the context of sperm biology, recent studies have shown that HSPA8 is produced by oviductal epithelial cells during sperm transport [5,6] and enhances boar, ram, and bull sperm survival [7][8][9][10] in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation